Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Certainly! Let's find the value of the polynomial [tex]\( p(x) = 4x^2 - 3x + 7 \)[/tex] for [tex]\( x = 1 \)[/tex].
Step 1: Start with the polynomial [tex]\( p(x) = 4x^2 - 3x + 7 \)[/tex].
Step 2: Substitute [tex]\( x = 1 \)[/tex] into the polynomial.
So, we have:
[tex]\[ p(1) = 4(1)^2 - 3(1) + 7 \][/tex]
Step 3: Calculate each term individually.
[tex]\[ 4(1)^2 \][/tex] simplifies to [tex]\( 4 \cdot 1 = 4 \)[/tex].
[tex]\[ -3(1) \][/tex] simplifies to [tex]\( -3 \)[/tex].
So, the expression becomes:
[tex]\[ p(1) = 4 - 3 + 7 \][/tex]
Step 4: Add the constants together.
[tex]\[ 4 - 3 + 7 = 1 + 7 = 8 \][/tex]
Therefore, the value of the polynomial at [tex]\( x = 1 \)[/tex] is [tex]\( 8 \)[/tex].
Step 1: Start with the polynomial [tex]\( p(x) = 4x^2 - 3x + 7 \)[/tex].
Step 2: Substitute [tex]\( x = 1 \)[/tex] into the polynomial.
So, we have:
[tex]\[ p(1) = 4(1)^2 - 3(1) + 7 \][/tex]
Step 3: Calculate each term individually.
[tex]\[ 4(1)^2 \][/tex] simplifies to [tex]\( 4 \cdot 1 = 4 \)[/tex].
[tex]\[ -3(1) \][/tex] simplifies to [tex]\( -3 \)[/tex].
So, the expression becomes:
[tex]\[ p(1) = 4 - 3 + 7 \][/tex]
Step 4: Add the constants together.
[tex]\[ 4 - 3 + 7 = 1 + 7 = 8 \][/tex]
Therefore, the value of the polynomial at [tex]\( x = 1 \)[/tex] is [tex]\( 8 \)[/tex].
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.